Community-Based Plastic Waste Management Through Simple Pyrolysis Technology and Biomass as an Alternative Heat Source - Sofiyulloh Sofiyulloh; Enik Sulistyowati (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2026)
Background: Plastic waste mismanagement in rural communities poses serious environmental and health threats, particularly when residents resort to open burning that releases toxic smoke. In Manikrejo Village, all household plastic waste—except bottles sold to scavengers—was either burned or discarded into the environment, with no prior community knowledge of plastic-to-fuel conversion technology. This community service program aimed to address this problem by introducing simple pyrolysis technology combined with locally sourced biomass as an alternative heat source. Purpose of the Study: The program aimed to empower the community through technical skills transfer, foster environmental awareness, and establish a sustainable, community-based plastic waste management system. Methods: A participatory community development approach was employed through four stages: initial observation, planning and preparation, workshop and training (three sessions, 12 hours total), and mentoring and evaluation (four weeks). A total of 25 community members participated in all stages, collaboratively constructing a simple pyrolysis reactor from recycled materials. Results: The program yielded significant outcomes. Participant knowledge increased substantially, with pre-test and post-test mean scores rising from 28.4 to 81.2—a gain of 52.8 points. Each 5 kg of plastic waste was successfully converted into approximately 3.5 liters of pyrolysis oil and 1 kg of biochar, with an optimum oil yield of 25.7% at 415°C. Evaluation demonstrated that 92% of participants were able to operate the reactor independently. The program also catalyzed the formation of a village waste management group, ensuring long-term sustainability.